Bovine bone particulates containing bone anabolic factors as a potential xenogenic bone graft substitute - David S. Musson; Ryan Gao; Maureen Watson; Jian-Ming Lin; Young-Eun Park; Donna Tuari; Karen E. Callon; Mark Zhu; Nicola Dalbeth; Dorit Naot; Jacob T. Munro; Jillian Cornish (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Alternative grafts are needed to improve the healing of bone non-union. Here, we assessed a bovine bone product which retains the inorganic and organic components of bone, as an alternative bone graft. Methods Bovine bone matrix proteins (BBMPs) were isolated from bovine bone particulates (BBPs) and tested in vitro. Primary rat osteoblast viability, differentiation, and mineralisation were assessed with alamarBlue®, real-time PCR, and von Kossa staining assays, respectively. Osteoclast formation was assessed in primary murine bone marrow cultures with TRAP staining. Human osteoblast growth and differentiation in the presence of BBPs was evaluated in 3D collagen gels in vitro using alamarBlue® and real-time PCR, respectively. The efficacy of BBPs as an alternative bone graft was tested in a rat critical-size calvarial defect model, with histology scored at 4 and 12 weeks post-surgery. Results In vitro, the highest concentration of BBMPs increased mineral deposition five-fold compared to the untreated control group (P < 0.05); enhanced the expression of key osteoblast genes encoding for RUNX2, alkaline phosphatase, and osteocalcin (P < 0.05); and decreased osteoclast formation three-fold, compared to the untreated control group (P < 0.05). However, the BBPs had no effect on primary human osteoblasts in vitro, and in vivo, no difference was found in healing between the BBP-treated group and the untreated control group. Conclusions Overall, despite the positive effects of the BBMPs on the cells of the bone, the bovine bone product as a whole did not enhance bone healing. Finding a way to harness the positive effect of these BBMPs would provide a clear benefit for healing bone non-union.